Children's rights : today's global challenge - Wall, John, 1965- (Blue Ridge Summit : Rowman & Littlefield Publishers, 2017)
"This accessible and authoritative book provides the first systematic overview of the global children's rights movement. It introduces both beginners and experts to child and youth rights in all their theoretical, historical, cultural, political, and practical complexity. In the process, the book examines key controversies about globalization, cultural relativism, social justice, power, economics, politics, freedom, ageism, and more. Combining vivid examples with cutting-edge scholarship, Children's Rights: Today's Global Challenge lifts up the rights of the youngest third of humanity as the major human rights challenge of the twenty-first century."--Publisher's website.
Why children's rights -- Theoretical controversies -- Historical ambiguities -- Education in an age of globalization -- The new child slavery -- The right to vote -- Today's global challenge.
Includes bibliographical references and index.
Keywords: Children's rights; Child labor; Child slaves; Children -- Legal status, laws, etc; Child labor; Child slaves; Children -- Legal status, laws, etc; Children's rights